Tuning the Stacking Modes of Ultrathin Two‐Dimensional Metal–Organic Framework Nanosheet Membranes for Highly Efficient Hydrogen Separation - Song, Shizheng; Wang, Wei; Zhao, Yali; Wu, Wufeng; Wei, Yanying; Wang, Haihui (Angewandte Chemie International Edition, 2023)
Two‐dimensional (2D) metal–organic framework (MOF) membranes are considered potential gas separation membranes of the next generation due to their structural diversity and geometrical functionality. However, achieving a rational structure design for a 2D MOF membrane and understanding the impact of MOF nanosheet stacking modes on membrane separation performance remain challenging tasks. Here, we report a novel kind of 2D MOF membrane based on [Cu 2 Br(IN) 2 ] n (IN=isonicotinato) nanosheets and propose that synergetic stacking modes of nanosheets have a significant influence on gas separation performance. The stacking of the 2D MOF nanosheets is controlled by solvent droplet dynamic behaviors at different temperatures of drop coating. Our 2D MOF nanosheet membranes exhibit high gas separation performances for H 2 /CH 4 (selectivity >290 with H 2 permeance >520 GPU) and H 2 /CO 2 (selectivity >190 with H 2 permeance >590 GPU) surpassing the Robeson upper bounds, paving a potential way for eco‐friendly H 2 separation.